Book Review: EDEN ROBINSON. Son of a Trickster. (2017) - Dobson, Kit (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2019)
EDEN ROBINSON. Son of a Trickster. Knopf. (2017). 319 pp. $32.00 (hardback). (ISBN 978-0-345-81078-6)